Research on Multi User MIMO Scheduling Algorithm Based on Hybrid Beamforming in 5G Communication - Xiang, Shihui (Journal of Theory and Practice in Engineering and Technology, 2024)
Massive MIMO is one of the core technologies in 5G communication, and multiple input multiple output signals can effectively improve the spectral efficiency and user communication quality in communication transmission. This article elaborates on the principle of effective channel transmission from two dimensions: user downlink channel and communication vector function, and designs a millimeter wave MIMO hybrid beamforming model based on this. The article analyzes the design principle, implementation steps, and algorithm complexity of millimeter wave hybrid beamforming model, and uses the hybrid beamforming model to design a specific implementation method for multi-user MIMO scheduling; Based on the model, determine the antenna weighting vectors for bidirectional alternating optimization of the transmitting and receiving terminal arrays, provide the algorithm flow for digital analog hybrid beamforming, and ultimately achieve balanced scheduling for multi-user MIMO. The simulation results show that the scheduling algorithm proposed in this paper has the advantages of fast convergence speed, low computational complexity, and high baseband transmission efficiency.